2018
DOI: 10.1002/ange.201711062
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilicity and Microsolvation of an Organic Molecule Resolved on the Sub‐molecular Level by Scanning Tunneling Microscopy

Abstract: Low-temperature scanning tunneling microscopy was used to follow the formation of asolvation shell around an adsorbed functionalizeda zo dye from the attachment of the first water molecule to af ully solvated molecule.S pecific functional groups bind initially one water molecule each, which act as anchor points for additional water molecules. Further water attachment occurs in areas close to these functional groups even when the functional groups themselves are already saturated. In contrast, water molecules s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…First, we heated the NaCl-precovered surface at different temperatures from room temperature (RT) to ∼500 K (the thermal treatment ensured the dissociation of Na + and Cl − on the surface 22−25 ) under a water environment at a pressure of ∼0.001 mbar. As water molecules can hardly adsorb on the Au(111) surface above RT, 26,27 they may only interact with the dissociated Na + and Cl − ions from the gas phase directly, as occurs in the Eley−Rideal process (cf. Scheme 1), while it was found that the NaCl square lattice was not perturbed and there is even no erosion of edges of NaCl islands (as shown in Figure 1), which thus indicates that the dissolution of NaCl via the ER process seems unfeasible.…”
mentioning
confidence: 99%
“…First, we heated the NaCl-precovered surface at different temperatures from room temperature (RT) to ∼500 K (the thermal treatment ensured the dissociation of Na + and Cl − on the surface 22−25 ) under a water environment at a pressure of ∼0.001 mbar. As water molecules can hardly adsorb on the Au(111) surface above RT, 26,27 they may only interact with the dissociated Na + and Cl − ions from the gas phase directly, as occurs in the Eley−Rideal process (cf. Scheme 1), while it was found that the NaCl square lattice was not perturbed and there is even no erosion of edges of NaCl islands (as shown in Figure 1), which thus indicates that the dissolution of NaCl via the ER process seems unfeasible.…”
mentioning
confidence: 99%